2017
DOI: 10.1111/ggi.13084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of healthcare utilization and life‐sustaining interventions between elderly patients with dementia and those with cancer near the end of life: A nationwide, population‐based study in Taiwan

Abstract: PwD in their last year of life in Taiwan underwent aggressive interventions significantly more frequently than did their counterparts in Western countries. Providing comfort-centered care for better quality of life for end-of-life PwD is a priority of Taiwan's national health policy. Geriatr Gerontol Int 2017; 17: 2545-2551.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
0
33
1
Order By: Relevance
“…In the control group of patients with cancer, 14.6% received tube feeding or intravenous fluids during the last day of life. In contrary to the findings in our study, Chen et al [ 16 ] found that patients with dementia were more likely to receive tube feeding compared to patients with cancer.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the control group of patients with cancer, 14.6% received tube feeding or intravenous fluids during the last day of life. In contrary to the findings in our study, Chen et al [ 16 ] found that patients with dementia were more likely to receive tube feeding compared to patients with cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…The number of patients with dementia receiving tube feeding or intravenous fluids during the last day of life was very low (3.5%) compared to findings in the literature from several countries. In an Italian study, 20.5% received tube feeding and 66.6% intravenous hydration during the last 48 hours in life [ 11 ], a Taiwanese study found that 67.4% of dementia patients received tube feeding during the last year in life [ 16 ] and Mitchel et al from the US found that 25% of demented residents died with a feeding tube compared with 5.2% of residents with terminal cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Taiwan have reported different patterns in the use of lifesaving procedures depending on patient diagnoses (i.e., dementia, cancer, or both) [28]. For instance, patients with dementia had a higher frequency of admission to the hospital and the ICU and a longer duration of hospitalization than those with cancer [6,29], indicating that a reduction in burdensome treatments among advanced dementia patients under palliative care among Taiwanese inpatients is more consistent among those with cancer. Furthermore, the proportion of cancer diagnoses was higher among the study patients than among dementia patients who did not receive palliative care [6].…”
Section: Service Evaluationmentioning
confidence: 99%
“…Two studies examined hospitalisation risk for people with dementia at the end of life with one Taiwanese register study of people in the last year of life reporting RR for admission 1.14 (0.91-1.41) and the other study of Finnish people with dementia in the final 2 years of life showing lower admission risk (RR = 0.33 (0.31-0.35)). There was low confidence in the evidence as the studies are of moderate and low quality respectively, and they present contradictory estimates [47,48]. Table 2 displays the rates of hospital admissions in people with dementia.…”
Section: Comparison To People Without Dementiamentioning
confidence: 99%